Exécution et mindgame dans les jeux vidéo de combat: les deux facettes de la vidéomotricité dans l`e-sport - Besombes, N. (Movement & Sport Sciences - Science & Motricité, 2018)
Esports refers to competitive videogaming. This phenomenon is growing in popularity and its comparison with sport is regularly debated. Many academic works have provided answers, whether in the field of sports science or media and game studies. These articles show that gamers` physical abilities are often perceived as the Achilles` heel of esports when compared to sport. Our work aims to highlight the gamers` physical abilities. Filmed observations focused on gamers` motor skills during eight esports gatherings and semi-directive interviews were conducted with four competitive fighting games players. Our results reveal that performing in esports depends on two inseparable skills. On one hand, players must automatize by repetition the various combinations of accurate and rhythmed inputs on their controllers (execution), and on the other hand, they must decode the opponent`s intentions on the graphic animations of the character he controls on the screen (mindgame). This ability to detect information on the virtual field, and to adapt real motor skills, presupposes the videogame incorporation.